Memória dos presos políticos no periodo ditatorial brasileiro - Pinheiro, Carlos Eduardo (2015)
This work aims to discuss the memory of former political prisoners and tortured. In the analysis of authors like Michael Pollak and Maurice Halbwachs is notorius agree that the memory is a construction made in this livings from the past, and therefore a reconstruction of the past and not a faithful and reporting of the facts. Looking systematize the memory of former political prisoners, with emphasis on the practice of torture during the dictatorial repression in Brazil. After the effective date of Law 11,255 / 95 created a place of memory for this group register its history and thus promote a confrontation with the official version. The analysis of documents collected by the Special Committee on Compensation implanted under the Law reveals the data obtained by the bureaucracy that determined the surveillance, information collection, arrest, and had as instrumental institutionalization of torture committed by its agents in public buildings. In this scenario, it brings to light the facts and characters in a battle that happened in Brazil and its consequences. It was also possible to establish from the documents, a brief profile of political activists persecuted by repression, public buildings where the military regime undertook its logic, the torture techniques and who were responsible for the implementation of the National Security Policy. Finally, we come across another discourse of national memory, where the former political prisoners overcome the stigma of 'enemies of the fatherland' foisted by the official version and now considered to be 'heroes of the democratic resistance'